تمثلات إيزابيل إبرهارت في رواية بدوي إيزابيل le bédouin d'isabelle لعبد القادر قرين - لعلايبية عبير وصال (My University, 2024)
Abstract : This study aims to introduce the Swiss traveler of aristocratic origins, Isabelle Eberhardt, who gave her life to defend Algerian society during the period of French occupation, in addition to the important role she played in his Algerian Cultural History book, through studying the representations of Isabelle Eberhardt in Badawi’s novel Isabel by Abdelkader Green, approved. In doing so, I relied on the objective approach and the field of serology, and through that I arrived at the positive, otherworldly image of Isabelle in Abdel Qader Qarin’s novel, and restored respect for this forgotten knight who lived and died in the heart of the desert, Ain al-Safra ---------------------- الملخص: تهدف هذه الدراسة إلى التعريف بالرحالة السويسرية ذات الأصول الأرستقراطية إيزابيل إبرهارت التي وهبت حياتها للدفاع عن المجتمع الجزائري في فترة تواجد الاحتلال الفرنسية بالإضافة إلى الدور المهم الذي لعبته في كتابه التاريخ الثقافي الجزائري وذلك من خلال دراسة تمثلات إيزابيل إبرهارت في رواية بدوي إيزابيل لعبد القادر جرين معتمدة في ذلك على المنهج الموضوعي وحقل الصرولوجيا فتوصلت من خلال ذلك إلى الصورة الآخرية الإيجابية لإيزابيل في رواية عبد القادر قرين وإعادة الاعتبار لهذه الفارسة المنسية التي عاشت وماتت في قلب الصحراء عين الصفراء. ----------------- Résumé : Cette étude vise à présenter la voyageuse suisse d'origine aristocratique, Isabelle Eberhardt, qui a donné sa vie pour défendre la société algérienne pendant la période de l'occupation française, outre le rôle important qu'elle a joué dans son livre Histoire culturelle algérienne, à travers l'étude des représentations de Isabelle Eberhardt dans le roman le bédouin d’isabelle d'Abdelkader Green, approuvé. Ce faisant, je me suis appuyé sur l'approche objective et le domaine de la sérologie, et grâce à cela je suis arrivé à l'image positive et surnaturelle d'Isabelle dans le roman d'Abdel Kader guerine et j'ai rétabli le respect. pour ce chevalier oublié qui a vécu et est mort au cœur du désert, Ain al-Safra
Keywords: : Isabelle Eberhart - the image - the self and the other - influence - travel literature; إيزابيل إبرهارت -الصورة -الأنا والآخر- تأثير تأثر - أدب الرحلة; Isabelle Eberhart - l'image - soi et l'autre - influence - littérature de voyage.